Facile fabrication of ZnO nanowire memory device based on chemically-treated surface defects. (12th February 2019) - Park, Woojin; Kim, Tae Hyeon; Nam, Jae Hyeon; Jang, Hye Yeon; Pak, Yusin; Min, Jung-Wook; Yun, Joho; Cho, Byungjin
Abstract: In this study, we demonstrate a transistor-type ZnO nanowire (NW) memory device based on the surface defect states of a rough ZnO NW, which is obtained by introducing facile H2 O2 solution treatment. The surface defect states of the ZnO NW are validated by photoluminescence characterisation. A memory device based on the rough ZnO NW exhibits clearly separated bi-stable states (ON and OFF states). A significant current fluctuation does not exist during repetitive endurance cycling test. Stable memory retention characteristics are also achieved at a high temperature of 85 °C and at room temperature. The surface-treated ZnO NW device also exhibits dynamically well-responsive pulse switching under a sequential pulse test configuration, thereby indicating its potential practical memory applications. The simple chemical treatment strategy can be widely used for modulating the surface states of diverse low-dimensional materials.